PENGARUH DIGITAL TRANSFORMATION DISCLOSURE DAN INTENSITAS R&D TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2024 - Yessi Octavia; Chandra Situmeang; Andri Zainal; Nasirwan Nasirwan; Erny Luxy D. Purba (JURNAL AKUNTANSI BARELANG, 2026)
This research seeks to explore and assess the impact of digital transformation disclosure and The impact of research and development (R&D) intensity on financial performance, as well as the moderating role of firm size in manufacturing companies listed on the Indonesia Stock Exchange in 2024. The study uses a cross-sectional design, purposeful sampling, and a quantitative technique. Multiple linear regression and moderated regression analysis (MRA) were used to assess the data, which came from the annual reports of businesses. Return on Assets (ROA) is a measure of financial success, whereas the inclusion of terminology related to digital transformation in annual reports is used to assess disclosure. Firm size is represented by the natural logarithm of total assets, while R&D intensity is denoted by a dummy variable. These results imply that R&D and digital transformation activities have not directly improved the short-term financial performance of manufacturing firms, and in larger firms, the benefits of digital transformation may not yet be fully reflected in improved financial performance. Keywords: Digital Transformation Disclosure, Intensitas R&D, Kinerja Keuangan dan Ukuran Perusahaan